2007
DOI: 10.1063/1.2464192
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics investigation of fluorocarbon based layer-by-layer etching of silicon and SiO2

Abstract: A molecular dynamics model is used to understand the layer-by-layer etching of Si and SiO2 using fluorocarbon and Ar+ ions. In these two-step etch processes, a nanometer-scale fluorocarbon passivation layer is grown on the material’s surface using low energy CFx+ ions or radicals. The top layers of the material are then reactive ion etched by Ar+ ions utilizing the fluorocarbon already present on the material surface. By repeating these two steps, Si or SiO2 can be etched with nanometer-scale precision and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 38 publications
3
65
0
Order By: Relevance
“…10). Similarly, the physical sputter yield data of SiO 2 for Ar + ion bombardment 95,122,124,128,[133][134][135][136][137] show significant scatter (see Fig. 11).…”
Section: Issues and Needsmentioning
confidence: 85%
See 4 more Smart Citations
“…10). Similarly, the physical sputter yield data of SiO 2 for Ar + ion bombardment 95,122,124,128,[133][134][135][136][137] show significant scatter (see Fig. 11).…”
Section: Issues and Needsmentioning
confidence: 85%
“…9 The molecular dynamics simulation of Rauf et al 95 first showed potential of a two-step etch process consisting of the formation of a nanometer-thick, self-limited fluorocarbon passivation layer on an SiO 2 or Si surface followed by etching with Ar + ions with energies up to 50 eV using the deposited fluorocarbon as a source of etchant. A sequence of these steps enabled nanometer precise etching of SiO 2 and Si.…”
Section: Iii-v: Gaasmentioning
confidence: 99%
See 3 more Smart Citations